JESUS CHRIST AS A MODEL FOR PEACE LEADERS IN ADVANCING CONFLICT TRANSFORMATION IN THE CITY OF SOLO - Irawan Budi Lukmono; Kezia Yemima (Manna Rafflesia, 2026)
As a pluralistic city, Solo is vulnerable to intolerance, violence, and conflict, all of which impact the lives of its residents. Ethnic, cultural, religious, and political divisions are the main causes of ongoing conflicts in Solo, resulting in frequent disturbances almost every year. The purpose of this study is to develop a peace leadership paradigm using Jesus Christ as a model to transform conflict in Solo. This research employs a qualitative methodology and a phenomenological paradigm. Data collection techniques include literature review, interviews, and observation. Domain analysis, taxonomic analysis, componential analysis, and thematic analysis were all used in the data analysis process. Based on the example of Jesus Christ, this study produces a peace leadership model aimed at bringing conflict transformation to Solo. Conclusion: In the context of Solo, peace leadership modeled on Jesus Christ is considered appropriate and applicable. .